PENGARUH KEPEMIMPINAN DAN DISIPLIN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING PADA KANTOR PUSAT PT. PERKEBUNAN NUSANTARA V DI KOTA PEKANBARU - Purba, Goklas Reinhard; Marnis, Marnis; Nas, Syakdanur (Jurnal Tepak Manajemen Bisnis, 2018)
This study aims to analyze the influence of leadership on employeemotivation and performance. The influence of discipline on employee motivationand performance. The influence of motivation on employee performance. theinfluence of leadership indirectly on employee performance with motivation asintervening variable. And the influence of discipline indirectly on the performanceof employees with motivation as a variable interveningThe population of research is head office employees at PT. PerkebunanNusantara V in Pekanbaru City is 150 people. The sample size that will be used is109 people. Data analysis using path analysis method (path analisys).The results of this study indicate that Leadership and discipline affect theMotivation. Leadership and motivation affect Performance. Leadership has asignificant effect on Employee Performance through Motivation. Discipline has asignificant effect on Employee Performance through Motivation. Motivationaffects Employee Performance